Explorations in agent-based simulation: analysis of Gini Index after zakat enforcement under interest based system - Putriani, Diyah; Mat Ghani, Gairuzazmi; Kartiwi, Mira (Fiscal Policy Agency, Minister of Finance, The Republic of Indonesia, 2019)
Voluminous previous studies show that zakah is able to reduce poverty and hence it is expected to minimize income inequality. At this point, there is one question remains, i.e., by how much level of Gini index can be reduced after zakah enforcement? Considering this gap of research, this study is proposed to capture the dynamic changes on Gini index after zakah enforcement. In this regards, zakah enforcement refers to a condition when zakah is received by all recipients. Since the existing economy is under interest-based system, thus there will be two scenarios in this research, i.e. the economy is run without and with zakah. From these two scenarios, it can be explored a potential reduction or increment on Gini index after zakah is disbursed to all recipients under interest-based system. This research fundamentally is an exploratory research; thus, many findings will be examined in the analysis. One of interesting findings is that in the long run only around 1 percent of total population own about 25 percent of total wealth in the economy without zakah. An Agentbased Computational Model (ABM) simulation will be employed to conduct the simulation. The application of ABM in this research is to bring the use of computational study as an alternative methodology to develop research in the area of Islamic economics.